Quantitative Assessment of Changes in Hemodynamics After Obliteration of Large Intracranial Carotid Aneurysms Using Computational Fluid Dynamics - Liu, Yongsheng; Jiang, Guinan; Wang, Feng; An, Xiangbo (Frontiers in Neurology, 2021)
Background: It was speculated that the alteration of the geometry of the artery might lead to hemodynamic changes of distal arteries. This study was to investigate the hemodynamic changes of distal arterial trees, and to identify the factors accounting for hyperperfusion after the obliteration of large intracranial aneurysms. Methods: We retrospectively reviewed data of 12 patients with intracranial carotid aneurysms. Parametric models with intracranial carotid aneurysm were created. Patient-specific geometries were generated by 3-dimentional rotational angiography. To mimic the arterial geometries after complete obliteration of the aneurysms, the aneurysms were virtually removed. The Navier-Stokes equations were solved using ANSYS CFX 14. The average wall shear stress, pressure and flow velocity were measured. Results: Pressure ratio values were significantly higher in A1 segments, M1 segments, and M2+M3 segments after obliteration of the aneurysms. (p= 0.048 in A1 segments, p= 0.017 in M1 segments, p= 0.001 in M2+M3 segments). Velocity ratio values were significantly higher in M1 segments and M2+M3 segments after obliteration of the aneurysms (p= 0.047 in M1 segments, p= 0.046 in M2+M3 segments). The percentage of pressure ratio increase after obliteration of aneurysms was significantly correlated with aneurysmal angle (r= 0.739, p= 0.006 for M2+M3). Conclusions: The pressure and flow velocity of distal arterial trees became higher after obliteration of aneurysms. The angle between the aneurysm and the parent artery was the factor accounting for pressure increase after treatment.